Concrete and relational vocabulary: comparison between Williams and Smith-Magenis syndromes - Garayzábal Heinze, Elena (2014)
We compared the performance of two clinical groups, Williams syndrome (WS) and Smith-Magenis syndrome (SMS), in terms of concrete and relational vocabulary. We analyzed (a) whether the WS group had an advantage in concrete vocabulary when compared to the SMS group, as good concrete vocabulary knowledge is considered a hallmark of WS; (b) if spatial processing difficulties in WS would be reflected specifically in their knowledge of relational spatial vocabulary; (c) if a specific vocabulary profile could be outlined for SMS.Our results show similar performances on receptive concrete and relational vocabulary in both groups. However, and as anticipated, performance on relational space concepts was significantly lower in the WS group.